Performance Evaluation of Proactive, Reactive and Hybrid Protocols by Varying Vehicle Nodes in Vehicular Ad-hoc Network - Chowdhury, N. M. Istiak; Goud, Madhav Kahar; Nahiyan, Md. Faqhrul Islam (International Journal of Computer Sciences and Engineering, 2025)
Routing protocols govern a network to facilitate the communication easier under specific network topology. Network researchers have presented various routing protocols for VANETs having different categories. Among these, the proactive, reactive and hybrid protocols are mostly prominent. Performance analysis of these routing protocols for MANET has been proposed earlier. But the main motive of this paper is to analyze the different performance metrics (throughput, end to end delay, routing overhead, packet delivery ratio, dropped packet) individually by which these protocols are compared in VANET. We have carried out the performance evaluation of Destination-Sequenced Distance Vector (DSDV), Zone Routing Protocol (ZRP), Dynamic Source Routing (DSR) and Ad-hoc On-Demand Distance Vector (AODV) as proactive, hybrid and reactive routing protocols, respectively, using NS2 simulator. In this paper, for simulation a particular scenario has been discussed. On the completion of this simulation we could have a clear view in what conditions VANET can be operated in more efficient manner compared to present VANET network arrangements. The simulation is performed on each routing protocol for varying vehicle nodes with source nodes 10 and 20.